2012
DOI: 10.2169/internalmedicine.51.7980
|View full text |Cite
|
Sign up to set email alerts
|

Osteomalacia due to a Bladder Reconstruction Performed 35 Years Previously

Abstract: We report a 54-year-old man with osteomalacia due to a bladder reconstruction performed 35 years previously. He had had slowly progressive chest and back pain for 18 months. Osteomalacia due to metabolic acidosis was suspected based on hyperalkalinephosphatasemia and a high serum chloride level, and the diagnosis was confirmed by bone scintigraphy. His symptoms and blood electrolyte levels were improved by oral medication, including sodium hydrogen carbonate. Measurement of the serum chloride level is simple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…The onset of symptoms after urinary diversion reportedly takes 2-11 years (9-12), our patient although had a long history of musculoskeletal pain, the diagnosis of metabolic bone disease was 31 years after the operation. Hirukawa et al has reported a patient with osteomalacia due to bladder reconstruction performed 35 years previously, the longest postoperative interval before the diagnosis and the highest chloride level in the literature (13). Our patient had moderately increased chloride level although there was a very long postoperative period at diagnosis.…”
Section: Discussionmentioning
confidence: 50%
“…The onset of symptoms after urinary diversion reportedly takes 2-11 years (9-12), our patient although had a long history of musculoskeletal pain, the diagnosis of metabolic bone disease was 31 years after the operation. Hirukawa et al has reported a patient with osteomalacia due to bladder reconstruction performed 35 years previously, the longest postoperative interval before the diagnosis and the highest chloride level in the literature (13). Our patient had moderately increased chloride level although there was a very long postoperative period at diagnosis.…”
Section: Discussionmentioning
confidence: 50%
“…La osteomalacia puede aparecer entre 2 y 4 años después de la intervención, si bien hay casos descritos hasta 35 años después 20,23 . Los pacientes con osteomalacia tras derivación urinaria mediante ileon o colon suelen tener niveles séricos elevados de Cl − y déficit de HCO3 − .…”
Section: Osteomalacia Y Enfermedad óSea Asociadas a Los Trastornos Hiunclassified
“…Hypophosphatemia—a condition in which osteomalacia is caused by impaired phosphorus absorption and reabsorption—is known to be caused by tumour-induced osteomalacia (TIO) and renal tubular acidosis 5 6. The FGF23 marker is useful for the diagnosis of TIO, as its levels are high in TIO patients and rapidly decrease after resection of the tumours responsible for the TIO 5.…”
Section: Differential Diagnosismentioning
confidence: 99%